The Rise in Single‐Mother Families and Children's Cognitive Development: Evidence From Three British Birth Cohorts. Issue 5 (20th November 2019) - Harkness, Susan; Gregg, Paul; Fernández‐Salgado, Mariña
Abstract : This article assessed changes in the association between single motherhood and children's verbal cognitive ability at age‐11 using data from three cohorts of British children, born in 1958 ( n  = 10, 675), 1970 ( n  = 8, 933) and 2000 ( n  = 9, 989), and mediation analysis. Consistent with previous studies, direct effects were small and insignificant. For those born in 1958 and 1970 indirect effects, operating through reduced economic and parental resources, were associated with −.107‐ SD to −.156‐ SD lower attainment. Differences between the two cohorts, and by children's age when parents separated, were insignificant. For the 2000 cohort, effect sizes for children born to single mothers did not change significantly (−.112‐ SD ) but attenuated for children whose parents separated in early childhood (−.076‐ SD ) or while of school age (−.054‐ SD ).